ANALISIS PENGGUNAAN TATA BAHASA DALAM PENYUSUNAN DOKUMEN PENAWARAN PROYEK KONTRUKSI PEMBANGUNAN GEDUNG FAKULTAS TEKNIK UPN “VETERAN” JAWA TIMUR - Larasati, Agistya Rachma; Ilham, Muhammad Nur; Jatmiko, Muhammad Fauzi; Wijianto, Yoga Pratama; Abidin, Farhan Zainul; Sholihatin, Endang (Universitas Sultan Ageng Tirtayasa, 2024)
This research analyzes the use of grammar in the preparation of project proposal documents for the construction of the Faculty of Engineering Building at UPN